Comparative Study of Carp Pituitary Gland (PG) extract and synthetic hormone ovaprim Used in the induced breeding of stinging catfish, heteropneustes fossilis(Siluriformes: Heteropneustidae) - Hossain, Md. Belal; Rahman, Md. Mosaddequr; Sarwer, Md. Golam; Ali, Md. Yusuf; Ahamed, Ferdous; Rahman, Sharmeen; Fulanda, Bernerd; Rahman, Mohammad Mustafizur; Raj Subba, Bharat; Hossain, Md. Yeamin (Nature Conservation and Health Care Council, 2012)

(untitled)
The present study compared the effectiveness of the Carp pituitary gland extract (PGE) and the synthetic hormone Ovaprim on spawning success of the stinging catfish, Heteropneustes fossilis during induced breeding. The PGE hormone was administered at 6 mg/kg of body weight for females and 2 mg/kg of body weight for males. In contrast, Ovaprim was administered at 0.3 ml/kg body weight and 0.1 ml/kg of body weight for females and males, respectively. The spawning success was higher in the Ovaprim-induced individuals with better performance recorded at all stages of spawning including latency period, ovulation, fertilization, hatching and incubation period compared to the PGE-induced individuals. In the Ovaprim induced individuals, the latency period occurred within 10 hours while in PGinduced individuals, the latency was after 15 hours. Similarly, ovulation rate was 90% for Ovaprim injected fish but lower 78.7% for PGE injected fish. Higher rate of fertilization was observed in the eggs of Ovaprim treated fishes 86.7% compared to 69.2% in PGE induced fish. On the other hand, hatching rate was 76.9% in eggs spawned from Ovaprim induced individuals compared to 72.7% in PGE induced fish and the incubation period was also shorter at 3.5 h for eggs from Ovaprim-induced fish while the PGE induced fish eggs required a 5-h incubation period. Finally, the results showed that Ovaprim treated fish yielded better results compared the PGE treated fish in terms of ovulation, fertilization and hatching rates of H. fossilis.